Competitiveness Management of Educational Services in Higher Education - Valentinovich Kosevich, Alexander; Olegovna Kozhina, Veronika; Viktorovna Pinkovskaya, Galina; Igorevna Rybyakova, Olga; Yevgenievna Lebedevaa, Olga (International Journal of Engineering and Technology, 2018)
The article substantiates key components of competitiveness management of educational services in higher education. The research outcomes have allowed identifying the main competitive advantages of educational services, which include the availability of additional educational services, the ability to participate in students’ exchange programs in home country and abroad, practical significance, assistance with employment, and reliable material and technical base. In the context of an integrated approach, the article proposes the organizational and economic mechanism for competitiveness management of educational services, which includes institutional support, economic security, social security, as well as technical and regulatory support. In order to solve the problem of inefficient use of financial resources, it is proposed to establish committees at the state level, the members of which will be representatives of the public sector, international community, and other experts in this field.